The data center construction of the Xinjiang Astronomical Observatory based on virtual observatory standards - Zhang, Hailong; Wang, J.; Demleitner, Markus; Ye, X.; Zhang, M.; Zhang, Y.; Wang, W.; Li, J.; Du, X. (Astronomy and computing, 2022)
As part of the Chinese National Astronomical Data Center, the Xinjiang Astronomical Observatory Data Center is built based on the virtual observatory standards. The data resources mainly include the pulsar dataset, the molecular spectral lines dataset, the intra-day variability source dataset generated by the Nanshan 25 m radio telescope, and the Nanshan 1 m wide-field telescope dataset, published through about a dozen data services, including a Table Access Protocol (TAP) endpoint. Some of these data services are registered with the International Virtual Observatory Alliance. Users can use standard virtual observatory tools, browsers, and scripts to retrieve all the metadata information in the data center and to realize simple data analysis, processing, and visualization operations.
Available online 18 April 202
Gesehen am 06.07.2022